Drivers of cyberbullying intention: a study on Malaysian undergraduates’ perspectives - Wong, Zhen Quan; Aw, Siew Ching; Beh, Si Ying; Tang, Su Wei; Yan, Chean Chai (2019)
With the availability of the Internet and social media, cyberbullying cases in Malaysia have increased rapidly in recent years and they subsequently become the serious issues that inhibit the healthy development of Malaysian youth, particularly local undergraduates. Actually, cyberbullying is an act which is committed deliberately at multiple times to harm other individuals through and ICT environment. Thus, cyberbullies’ behaviour arises as a result of one’s intention which is caused by certain determinants. Apparently, the determinants that significantly influence an individual’s behavioural intention towards cyberbullying in this study are referred to the theory of planned behaviour (TPB) constructs and empathy. Hence, this research is aimed to determine whether the TPB and personality trait (i.e. empathy) can be used to explain the behavioural intention towards cyberbullying among Malaysian undergraduates. The self-administered questionnaires are delivered to 258 undergraduates who study in top 5 Malaysian universities. The research results have shown that attitude, subjective norms and perceived behavioural control have a positive relationship with behavioural intention towards cyberbullying. However, empathy is the only one independent variable that is found to have no significant association with dependent variable. Based on the research findings, attitude can be considered as the most significant predictor of behavioural intention towards cyberbullying when comparing to other independent variables which have been investigated in this study.